Z’s Privacy Calculus on Using a Second Instagram Account - Lutfi Kurniawan, Andika; Hidayanto, Syahrul (Green Publisher, 2024)
This research aims to understand Gen Z's use of the privacy calculus on second Instagram accounts and discover what advantages and risks Instagram users gain from self-disclosure. This research uses a qualitative method with a descriptive approach. The author used a purposive sampling technique, where informants were determined deliberately based on criteria, namely Instagram users aged 11 - 24 years and from Jakarta. The data collection techniques used were interviews, observation, and documentation. Data analysis uses the Miles and Huberman model, which consists of data reduction, presentation, and conclusion. The results show that a second Instagram account can pose a greater risk than the benefits felt by the user, due to a lack of awareness regarding privacy uploads, so that privacy issues depend on the awareness and control of the account owner. Research still needs to be more extensive in generalizing data. For this reason, quantitative research related to themes is needed in the future. Instagram users can increase their awareness by expressing themselves through second accounts. Apart from that, researchers can also provide an overview of the benefits and risks obtained after disclosing themselves via a second Instagram account to provide advice regarding healthy use of social media. A second Instagram account can still pose a risk. However, many second Instagram account users are still active in using the second account. Several risks, namely security risk, stigma risk, and role risk. Meanwhile, the perceived benefits are self-expression, social validation, and relationship development.